PERAN PROMOSI MELALUI INFLUENCER DALAM MENINGKATKAN MINAT GENERASI Z MENGGUNAKAN PRODUK PERBANKAN SYARIAH - Fathiyyah, Dewi Fatihatun; Wahidullah; Nafisah, Zahrotun (Wahana Islamika Jurnal Studi Keislaman, 2025)
This study aims to analyze the role of promotion through influencers in increasing Generation Z's interest in Islamic banking products. This study uses a descriptive qualitative approach with an in-depth interview method with 51 respondents consisting of Generation Z, influencers, and Islamic banking practitioners. The results of the study indicate that promotion through influencers can increase knowledge and appeal of Islamic banking products, with an average respondent interest score of 4.16. The main factors that influence the effectiveness of promotion are the credibility of influencers, the quality of promotional messages, and the relevance of products to consumer needs. However, the effectiveness of this promotion is still limited in changing consumer preferences from conventional to Islamic banking. Recommendations provided include selecting credible influencers, improving the quality of promotional messages, and integrating educational campaigns to strengthen understanding of the advantages of Islamic banking. This study provides strategic insights for Islamic banks in utilizing digital marketing to increase Generation Z participation.